Stepping through Origins : Nature, Home, and Landscape in Irish Literature - Holdridge, Jefferson (Book collections on Project MUSE., 2021)
""Stepping through Origins" addresses the place of the aesthetics of nature, landscape, and family in Irish literature, aiming to show how nature is associated with a complex web of Original Sin, colonial conquest, and Oedipal guilt, and how finally some contemporary writers in their acknowledgement of the ecological movement have moved beyond this construction"--